Reform of the international financial architecture: An Asian perspective - Masahiro Kawai (Asian Development Bank Institute (ADBI), 2009)
It has taken two crises - the Asian financial crisis of 1997-1998 and the global financial crisis of 2007-2009 - for the international community to seriously focus on the reform of the international financial architecture for crisis prevention, management and resolution. Facing the global financial crisis, the international community has responded by making the G20 Summit the premier forum for international economic and financial cooperation, creating a potentially more powerful Financial Stability Board, and augmenting the financial resources of the IMF. However, the international financial architecture remains inadequate for the needs of many emerging market economies. The effectiveness of IMF surveillance - particularly that of systemically important economies (such as the US, the UK and the Euro Area) - as well as its governance structure should be improved. International liquidity support should be made available when any country with sound economic and financial management is put into an externally driven crisis. International agreements should be reached on external (sovereign) debt restructuring, and on the cross-border resolution of insolvent, internationally active financial firms for fair burden sharing of losses between creditors and debtors, or among different national authorities. A well-functioning regional financial architecture could complement and strengthen the international financial architecture. East Asian authorities should focus on: (i) the establishment of resilient national financial systems, including local-currency bond markets; (ii) integration of national financial markets to facilitate the mobilization of regional savings for regional investment (in infrastructure and SMEs); and (iii) enhancement of regional liquidity (Chiang Mai Initiative Multilateralization) and economic surveillance mechanisms. The region should also intensify regional exchange rate policy coordination to achieve sustained economic growth without creating macroeconomic and financial instability.
Keywords: F30; F32; F33; F34; F53; F55; 330; Finanzmarktkrise; Internationaler Finanzmarkt; Kapitalmobilität; Internationales Währungssystem; Regulierung; Aufsichtsbehörde; Internationale Wirtschaftsorganisation; Asien; Welt